Structural Dynamics Concepts and Applications. - Busby, Henry R.; Staab, George H. (Milton : Chapman and Hall/CRC, 2017)
"Structural Dynamics: Concepts and Applications focuses on dynamic problems in mechanical, civil and aerospace engineering through the equations of motion. The text explains structural response from dynamic loads and the modeling and calculation of dynamic responses in structural systems. A range of applications is included, from various engineering disciplines. Coverage progresses consistently from basic to advanced, with emphasis placed on analytical methods and numerical solution techniques. Stress analysis is discussed, and MATLAB applications are integrated throughout. A solutions manual and figure slides for classroom projection are available for instructors."--Provided by publisher.
1.11.5 An Application of U*1.11.6 Experimental Determination of U*; Problems; References; 2. Random Vibrations; 2.1 Introduction; 2.2 Probability, Probability Distribution, and Probability Density; 2.3 Mean, Variance, Standard Deviation, and Distributions; 2.4 Combined Probabilities; 2.5 Random Functions; 2.5.1 Correlation Function and Spectral Densities; 2.5.2 Combinations of Random Processes; 2.5.3 Level Crossings; 2.6 Dynamic Characteristics of Linear Systems; 2.7 Input-Output Relations for Stationary Random Processes; 2.8 Input-Output Relations for Nonstationary Random Processes; Problems
Description based upon print version of record.
4.3.1 Generalized Forces
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING / Structural